Contextual Analysis of ICT Contents in LIS Postgraduate Degree Curriculum: A Study - Tyagi, Uma; Yanthan, Zuchamo (DESIDOC Journal of Library & Information Technology, 2016)
The content of Library and Information Science (LIS) curriculum has drastically evolved in the recent decades. With the penetration of Information and Communication Technology (ICT), technological components have becomes the main focus of the discipline. The present paper analyses the ICT contents of postgraduate degree courses in select universities across India. It also analyses the expectation of the professionals with regard to course content and relevancy of the curriculum in the contemporary times. The present study system suggests that maintaining homogeneity and standardised curriculum will help in keeping Indian syllabi at par with international standards.